The tooth morphology of juvenile Pacific nurse sharks Ginglymostoma unami (Chondrichthyes: Ginglymostomatidae) - Seifert, Jesco (Journal of Fisheries, 2025)
Nurse sharks (family Ginglymostomatidae) are a small group of sharks that currently consists of four different species. These species are distributed all over the globe, each occupying a specific geographical region. The last described nurse shark species, the Pacific nurse shark (Ginglymostoma unami), is found exclusively on the West coast of America from the Southwest of Baja California and the Gulf of California (Mexico) to Peru. This species was previously synonymized with the Atlantic nurse shark (Ginglymostoma cirratum), but described as separate in 2015. For this reason, some data on tooth morphology, especially that of juvenile individuals, is missing. This study examines a jaw of a juvenile Pacific nurse shark and shows the change in the tooth morphology of this species over the course of its life. In addition, this work compares the tooth morphology of the different nurse shark species and provides an overview of how they can be differentiated.